Metabolismo energético e termorregulação do tucano-toco (Ramphastos toco) - Chaves, Jussara Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Body temperature regulation in endotherms involves adjustments in heat exchange rates between the animal and the environment. One of those mechanisms include the modulation of the surface temperature of specific areas of the body through vasomotor adjustment promoting dissipation or conservation of body heat. This thermoregulatory adjustment is essential for maintenance of body temperature over a moderate temperature range, known as thermal neutral zone (TNZ), without increasing the metabolic rate (MR). Thermal windows are body regions poorly insulated and highly vascularized that are particularly efficient for heat dissipation through that mechanism. The beak of the toco-toucan (Ramphastos toco) was described as a highly efficient thermal window, assisting the thermal homeostasis of this bird. Therefore, is possible that the heat exchange adjustments through the beak have an important role on delimitation of TNZ. Hence, our goal in this study was to determinate the contribution of heat exchanges through de beak of R. toco on the amplitude and limits (lower and upper) of TNZ. For that, we measured metabolic rate, through oxygen consumption, over a range of ambient temperature from 0 to 35°C (every 5°C). MR measurements were made in birds with the beak intact (control group) and subsequently with the beak artificially insulated (experimental group). The limits of TNZ, 9.5-25.0°C for the control group and 10.8-23.3°C for the experimental group, did not differ between the treatments. MR differed among treatments only at elevated temperatures (30 and 35°C), reaching values of 0.97 mlO2.g -1.h-1 (± 0.06) for the control group and 1.20 mlO2.g -1.h-1 (± 0.07) for the experimental group at 35°C. These results indicate that under high temperatures, the insulation of the beak compromised the heat exchange with the environment, so the MR increased above normal to dissipate ... (Complete abstract click electronic access below)

A regulação da temperatura corpórea dos endotérmicos envolve ajustes na taxa de troca de calor entre o animal e o ambiente. Um destes mecanismos consiste na modulação da temperatura superficial de áreas específicas do corpo via ajustes vasomotores para promover conservação ou dissipação do calor corpóreo. Este ajuste termorregulatório é fundamental para manutenção da temperatura corpórea ao longo de uma faixa de temperatura moderada, denominada Zona de Neutralidade Térmica (ZNT), sem aumento da taxa metabólica (TM). As janelas térmicas, regiões do corpo pouco isoladas e altamente vascularizadas, são muito eficientes na dissipação de calor corpóreo através desse mecanismo. O bico do tucano-toco (Ramphastos toco) foi descrito como uma janela térmica altamente eficiente, atuando de forma muito relevante na homeostase térmica dessa ave. Por isso, é possível que os ajustes na troca de calor através do bico desempenhem um papel central na delimitação da ZNT desta ave. Portanto, o objetivo do presente trabalho foi determinar a contribuição das trocas de calor através do bico de R. toco nos limites superior e inferior da ZNT. Para tal, medimos a taxa metabólica dos tucanos ao longo de uma faixa de temperatura ambiente de 0 a 35°C (a cada 5°C). As medições de TM foram feitas com o bico em sua condição intacta (grupo controle) e, posteriormente, com o bico isolado artificialmente (grupo experimental). O limites da ZNT, 9,5 - 25,0°C para o grupo controle e 10,8 - 23,3°C para o grupo experimental, não diferiram entre os tratamentos. A TM diferiu entre os tratamentos somente sob temperaturas elevadas (30 a 35°C), atingindo valores de 0,97 mlO2.g-1.h-1 (±0,06) para o grupo controle e 1,20 mlO2.g-1.h-1 (±0,07) para o grupo experimental a 35°C. Estes resultados indicam que, sob temperaturas elevadas, o isolamento do bico comprometeu as trocas de calor com ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ave; Tucano; Temperatura corporal - Regulação; Metabolismo; Homeostase; Birds